Gene duplication and deletion caused by over-replication at a fork barrier - Judith Oehler; Carl A. Morrow; Matthew C. Whitby (Nature Communications, 2023)
Abstract Replication fork stalling can provoke fork reversal to form a four-way DNA junction. This remodelling of the replication fork can facilitate repair, aid bypass of DNA lesions, and enable replication restart, but may also pose a risk of over-replication during fork convergence. We show that replication fork stalling at a site-specific barrier in fission yeast can induce gene duplication-deletion rearrangements that are independent of replication restart-associated template switching and Rad51-dependent multi-invasion. Instead, they resemble targeted gene replacements (TGRs), requiring the DNA annealing activity of Rad52, the 3’-flap nuclease Rad16-Swi10, and mismatch repair protein Msh2. We propose that excess DNA, generated during the merging of a canonical fork with a reversed fork, can be liberated by a nuclease and integrated at an ectopic site via a TGR-like mechanism. This highlights how over-replication at replication termination sites can threaten genome stability in eukaryotes.